2017
DOI: 10.1037/hea0000427
|View full text |Cite
|
Sign up to set email alerts
|

The psychological challenges of living with an ileostomy: An interpretative phenomenological analysis.

Abstract: CHALLENGES FOR PERSONS WITH AN ILEOSTOMY 2The psychological challenges of living with an ileostomy:an interpretative phenomenological analysis Abstract Objectives: Ileostomy, in which the small intestine is re-directed out of an abdominal wall so that waste is collected using a bag, is used to treat conditions including Inflammatory Bowel Disease and colorectal cancer. This paper reports an in depth idiographic analysis of the experience of living with an ileostomy. Methods: 21 participants took part in semi-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 33 publications
2
46
0
1
Order By: Relevance
“…Consequently, instead of hiding the bag, the person showed it without fear of rejection. These results are in line with the study of Smith et al (2016), who reported that the relationship between ileostomy patients and their family and friends is often challenged by the new condition/status and that family and social support, when present, helps the person living with an ileostomy. When talking about the activities carried out with friends, for example playing football, there is a clear perception of the difference.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Consequently, instead of hiding the bag, the person showed it without fear of rejection. These results are in line with the study of Smith et al (2016), who reported that the relationship between ileostomy patients and their family and friends is often challenged by the new condition/status and that family and social support, when present, helps the person living with an ileostomy. When talking about the activities carried out with friends, for example playing football, there is a clear perception of the difference.…”
Section: Discussionsupporting
confidence: 81%
“…This does not mean that the patient was satisfied with his diagnosis and the need for an ileostomy, but rather that he had positive expectations about the future resolution of his situation. This result is in line with the study of CARLA REGINA RODRIGUES DA SILVA et al Smith, Spiers, Simpson, and Nicholls (2016), in which stoma surgery was found to have a positive impact on patients if it mitigates previous symptoms, thus improving their quality of life. In view of the above, a transition is influenced by the internal and external conditions of the person who experiences it.…”
Section: Discussionsupporting
confidence: 81%
“…This process was conducted not in order to reach a consensus, but to encourage reflection upon the analysis, and to identify any potential areas that might have been GUIDED SELF HELP FOR EATING DISORDERS 10 influenced by assumptions (Yardley, 2014). It is an important process for ensuring the credibility of the final account (Smith, Spiers, Simpson & Nicholls, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…IPA was developed within psychology and it aims to provide detailed examinations of personal lived experience in its own terms rather than using preexisting theoretical preconceptions (e.g., Smith, 2017). IPA subscribes to a hermeneutic phenomenology where both participant and researcher are recognized as sense-making agents (Cassidy, Reynolds, Naylor, & De Souza, 2011;Smith, 2004Smith, , 2011Smith, , 2017Smith, Flowers, & Larkin, 2009;Smith, Spiers, Simpson, & Nicholls, 2017). The key theoretical perspectives of IPA are phenomenology, interpretation (hermeneutics), and idiography.…”
Section: Methodsmentioning
confidence: 99%
“…The key theoretical perspectives of IPA are phenomenology, interpretation (hermeneutics), and idiography. For IPA, phenomenology involves hermeneutics, which is defined as the theory and practice of the interpretation of the meaning of texts (Smith, 2011(Smith, , 2017Smith et al, 2009;Smith et al, 2017). The IPA approach has a "practical" orientation and is therefore suitable for physiotherapy researchers (Cassidy et al, 2011).…”
Section: Methodsmentioning
confidence: 99%